One-month assessment of Th-cell axis related inflammatory cytokines, IL-17 and IL-22 and their role in alcohol-associated liver disease - Sagaram, Manasa; Frimodig, Jane; Jayanty, Danielle; Hu, Huirong; Royer, Amor J.; Bruner, Ryne; Kong, Maiying; Schwandt, Melanie L.; Vatsalya, Vatsalya (Frontiers in Immunology, 2023)
Changes in the expression of cyto- and chemokines due to alcohol-associated liver disease (ALD) have been reported to be both protective and pathogenic. This study examined plasma levels of two key cytokines, Il-17 and Il-22 that construct the pro-inflammatory vs. anti-inflammatory axes across the spectrum of alcohol use disorder (AUD) and ALD including alcohol-associated hepatitis (AH) to determine the underlying status of the inflammation. Forty-two males and females aged 25-63 yrs. were grouped as healthy controls (HV[n=8]), AUD with no liver injury (AUDNLI [n=8]), AUD with liver injury (AUDLI [n=8]), non-severe alcohol-associated hepatitis (NSAH [n=9]), and severe alcohol-associated hepatitis (SAH [n=9]). Demographic, drinking, and clinical data were collected. Blood samples were collected at baseline (BL, all subjects) and during week 4 (W4, only patients) for IL-17 and IL-22; and statistically analyzed. IL-17 was highly elevated in the SAH group at BL and post-SOC. LTDH and BL IL-22 in non-severe AH patients were associated significantly. LTDH significantly predicted W4 IL-22 levels, positively (increasing) in NSAH and inversely (lowering) in SAH patients. BL and W4 IL-22 levels were significantly higher (4-fold, p≤0.001) in all AH patients compared to all AUD patients (AUROC=0.988, p≤0.001). IL-22 showed significant affinity with AST, AST: ALT ratio, total bilirubin, INR, and PT both at BL and W4. IL-22 was inversely associated with IL-1β; and positively with TNF-α and IL-8 both at BL, and W4. BL IL-17 showed a positive correlation with MELD (p=0.017) in all AH patients. In SAH, > 2-fold W4 IL-17 level compared to BL showed significant within subjects’ effects, p=0.006. In AUD patients without AH, the drop in IL-17 at W4 vs. BL showed a significant within subjects’ effect, p=0.031. Drinking chronicity predicted opposite effects in IL-22 levels in NSAH (anti-inflammatory) and SAH (pro-inflammatory) at post-SOC. BL IL-22 levels differentiated AH patients robustly from the AUD patients (with or without liver injury); and showed corresponding stepwise increases with the stages of ALD. IL-22 was closely associated with progression and injury markers of the liver; and response to the pro-inflammatory cytokines. Pro-inflammatory IL-17 showed a strong positive association with MELD, a severity indicator of AH.